The Physicochemical Dynamics of Epie Creek, Yenagoa, Bayelsa State, Nigeria - Domokuma, Oweifa Munasuonyo; Joe, Alagoa Koru (International Journal of Scientific Research in Biological Sciences, 2024)
The Physicochemical Dynamics of Epie Creek, Yenagoa, Bayelsa State was investigated. This was done to measure the degree of direct and indirect human impacts on receiving systems of Epie creek, Bayelsa State. Physicochemical samples were collected for analyses once monthly from Four (4) stations for twelve (12) consecutive months between April 2021 and March 2022. Samples were collected between the hours of 08:00hrs to 12:00hrs during each sampling day using standard techniques. Physicochemical samples were analyzed for Biochemical Oxygen Demand (BOD5), Dissolved Oxygen (DO), Alkalinity, Temperature, pH and Electrical conductivity (EC). Means and standard deviation were calculated for all physicochemical variables for both dry and wet seasons. Physicochemical data were subjected to analysis of variance (ANOVA) at the 95% confidence limit (P=0.05) in order to check the sources of variability and similarities in the measured values at stations within seasons. T-test was employed to determine the degree of variability of physicochemical parameters between seasons. This was aided by the SPSS® 20.0 statistics tool kit. Results indicate that all the physicochemical parameters were within the internationally permissible threshold for physicochemical parameters in fresh water. There were significant differences (P<0.05) of certain physicochemical parameters between the wet and dry seasons and between stations. It can be concluded that Epie creek in not under any immediate threat of pollution and the current practices around the creek be sustained or improved upon.